Psychometric properties of the scale for non-adherence to antiretroviral medication (NAME) among HIV-infected patients - Zahra Hosseini; Hassan Eftkhar; Teamur Aghamolaei; Abbas Ebadi; Saharnaz Nedjat; Ladan Abbasian; Mina Hashemiparast (BMC, 2019)
Abstract Background Adherence to HIV medication is necessary for long-term HIV disease management. The objective of this study was to develop and examine the psychometric properties of a scale for measuring the barriers of antiretroviral medication adherence among Iranian Patients. Method This was a sequential, exploratory mixed methods investigation composed of two phases. In the qualitative phase, item pool generation and questionnaire designing was carried out through in-depth individual interviews and group discussions; in the quantitative phase, psychometric properties of the questionnaire were assessed. In both phases, the participants were people who were living with HIV/AIDS and were taking antiretroviral medications. Results In the first phase, an item pool containing 181 statements related to barriers of adherence to antiretroviral medication was generated. In the second phase, item reduction was applied, and a questionnaire containing 30 items was developed. The psychometric properties of the questionnaire were assessed, which indicated good validity and reliability of the instrument. In exploratory factor analysis, the items were loaded on six factors that altogether explain for 61.98 of the variance. The Cronbach's alpha and the intra class correlation coefficient of the questionnaire was 0.91 and 0.80, respectively. Conclusion This study provided a reliable and valid instrument to identify the barriers of adherence to antiretroviral medication in patients with HIV/AIDS. Identify these barriers and design of interventions to eliminate or reduce of barriers can be an effective means of enhancing adherence to antiretroviral medication among these patients.